Electrophysiology of type II mesangiocapillary glomerulonephritis with associated fundus abnormalities. Issue 12 (December 1993) - O'Brien, C; Duvall-Young, J; Brown, M; Short, C; Bone, M
Abstract : The retinal electrophysiology is reported in four patients with type II mesangiocapillary glomerulonephritis and partial lipodystrophy with associated fundus abnormalities and no visual symptoms. The histological hallmark of the condition is that of widespread electron dense deposits in the renal glomerulus and in the choriocapillaris and Bruch's membrane of the eye. Three of the four patients had the typical fundal appearance of multiple, yellow, drusen-like lesions at the posterior pole of the eye with normal visual acuity. These three patients had abnormally low Arden ratios on electro-oculography with normal electroretinography responses. This is the first clinical model of disease known to be isolated to the choriocapillaris and Bruch's membrane causing an electro-oculographic abnormality without any clinically detectable deficit in visual function.